Temperature, light, direction of currents and selected water quality parameters at coral reef sites within Talang-Satang MPS - Ng, Chiew Tyiin (Universiti Malaysia Sarawak, UNIMAS, 2012)
Coral reefs around the world are being increasingly threatened by the increase in sea water temperature. Therefore Temperature / Light logger and G Acceleration Logger were deployed to record temperature, light intensity and direction of current flow every twenty minutes for eight months at west of Pulau Talang Talang Besar, Sarawak. Other selected water quality parameters were also recorded at four stations within Talang- Satang MPA. Three regimes, Regime A, Regime B and Regime C each corresponding to the Southwest monsoon (May to September), intermonsoon (September to November) and Northeast monsoon (November to March) was distinguished based on the tidal cycle and large changes in direction of current during intermonsoon. Temperature and light intensity were found to decrease as the monsoon changes from Southwest monsoon to Northeast monsoon. The direction of current was found to have the highest variability during intermonsoon and the velocity of current was higher during monsoon seasons, corresponding to the larger change in hydrodynamics of the water column. It was also found that there was a positive correlation between light intensity and temperature throughout the eight months. Temperatures as high as 31.3˚C were recorded during Southwest monsoon (July to September). High water temperatures from 30.8˚C to 31.3˚C were recorded for 23 days and change in 1.0˚C of water temperature in a day was recorded during Northeast monsoon (November to March). The overall water quality of Talang-Satang MPA was found to be suitable for healthy coral reefs and there was no significant change in water quality between the two surveys (July 2011 and April 2012).